2013
DOI: 10.5558/tfc2013-068
|View full text |Cite
|
Sign up to set email alerts
|

Tree species selection revisited for plantations in the Interior Cedar Hemlock zone of southern British Columbia

Abstract: We provide results from two trials comparing performance of species of known provenance planted on logged sites in the southern Interior Cedar Hemlock biogeoclimatic zone of southern British Columbia 20 and 26 years after establishment. The commonly used plantation species, lodgepole pine (Pinus contorta var. latifolia), interior spruce (a naturally occurring hybrid between Picea glauca and P. engelmannii) and Douglas-fir (Pseudotsuga menziesii var. glauca), survived as well as, but grew more slowly than, west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Such effective resistance responses in western redcedar at the root level probably contribute to low mortality in western redcedar compared to other common conifers when growing in mixed stands. In a 20‐year‐old species trial in the ICH southern interior, Vyse et al (2013) reported mortality in Douglas‐fir and western larch was 7 and 10 times greater, respectively, than in western redcedar. Furthermore, results from a long‐term stumping trial showed mortality in western redcedar to be significantly lower than other planted conifers such as Douglas‐fir and western larch (Cleary et al, 2013; Cruickshank et al, 2018; Morrison et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such effective resistance responses in western redcedar at the root level probably contribute to low mortality in western redcedar compared to other common conifers when growing in mixed stands. In a 20‐year‐old species trial in the ICH southern interior, Vyse et al (2013) reported mortality in Douglas‐fir and western larch was 7 and 10 times greater, respectively, than in western redcedar. Furthermore, results from a long‐term stumping trial showed mortality in western redcedar to be significantly lower than other planted conifers such as Douglas‐fir and western larch (Cleary et al, 2013; Cruickshank et al, 2018; Morrison et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…shows considerable resistance to the fungus, but only after it reaches about 20–25 years of age (Robinson & Morrison, 2001). However, in young regenerating stands, mortality in western larch can be extremely high, exceeding that observed in Douglas‐fir (Vyse et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Variations in quantitative resistance to Armillaria species have been investigated both among (e.g. Ferguson et al 2003;Baumgartner et al 2011;Vyse et al 2013), and within (e.g. Baumgartner & Rizzo 2006;Solla et al 2011;Cruickshank & Jaquish 2014) host species.…”
Section: Silvicultural Measuresmentioning
confidence: 99%
“…Environmental services of trees are no doubt having unquantifiable global notability benefits but the choice of many trees may limit their potential. The pressing need of trees for environmental quality restoration and improvement is a global goal, and good candidate character is in its highly adaptability and resistance to degrading agents [2,3]. Triplochiton scleroxylon (Family: Sterculiaceae) also known as obeche and Arere in Yoruba land and few indigenous trees like Delonix regia and Khaya spp.…”
Section: Introductionmentioning
confidence: 99%